Comparative analysis of conventional and greener extraction methods and method validation for analyzing PAHs in cooked chicken and roasted coffee. (1st December 2021) - Singh, Lochan; Agarwal, Tripti
Highlights: PAH recoveries using conventional methods deviated from EU accepted criteria. Recoveries of Heavy PAHs by SUPRAS ranged from 71.33 to 112.23% in chicken. Baseline shift in coffee samples prepared with SUPRAS. PAHs' recoveries in chicken and coffee by QuEChERS were 62.3–103.9% and 52.6–78.7%. SUPRAS and QuEChERS needed 69–139 fold lower energy than conventional methods. Abstract: This study compared different extraction methods [sonication, alkaline hydrolysis, supramolecular solvent microextraction (SUPRAS) and Quick, Easy, Cheap, Effective, Rugged and Safe (QuEChERS)] along with their greenness. An analytical method was validated for determination of USEPA's listed 16 polycyclic aromatic hydrocarbons' (PAHs) in cooked chicken and roasted coffee using high pressure liquid chromatography-fluorescence detector (HPLC-FLD) with a C18 column. The recoveries with QuEChERS ranged between 62.26 and 103.85% (except Naphthalene and Fluorene) and 52.63–78.69% (except Naphthalene) for chicken and coffee respectively while poor recoveries were observed with conventional methods. With SUPRAS, heavy PAHs' recovery in chicken was 71.33–112.23%. Limits of detection (LOD) were 0.03–0.06 ng/mL, regression coefficient values were 0.97–0.99 for 6.25–37.50 ng/mL quantification range. Relative standard deviation was found to be below 22%. The time and energy consumption per sample was 42.50 and 69.06 fold and 77.52 and 139.50 fold less with SUPRAS and QuEChERS method respectively as compared to alkaline hydrolysis.